2014
DOI: 10.1016/j.proeng.2014.11.466
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Efficiency for Variable Speed Pumps in EPANET Compared with Experimental Data

Abstract: Our paper aims at assessing the way in which EPANET estimates the efficiency of variable speed pumps operating at speeds different from the nominal speed. An experimental setup, existing at the Technical University of Civil Engineering Bucharest, was modelled in EPANET 2. The facility allows the measurement of the characteristic curves of two identical pumps driven by electric motors with the rotational speed ratio of ½. The pumps curves were fed into EPANET and results for different rotational speeds were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 5 publications
0
17
0
1
Order By: Relevance
“…The free-water surface adopts the steel cover theorem to use the outflow and uses the symmetrical boundary condition. The export condition is free flowing; the fluid and the wall have no slip [28][29][30][31][32]. The pump station forebay grid map is shown in Figure 11(a).…”
Section: Grid Division and Sensitivity Verificationmentioning
confidence: 99%
“…The free-water surface adopts the steel cover theorem to use the outflow and uses the symmetrical boundary condition. The export condition is free flowing; the fluid and the wall have no slip [28][29][30][31][32]. The pump station forebay grid map is shown in Figure 11(a).…”
Section: Grid Division and Sensitivity Verificationmentioning
confidence: 99%
“…Because EPANET 2.0 power calculation for variable speed pumps are not correct [19,20], power consumption is calculated within MS Excel using the affinity laws and the pump efficiency curves for nominal speed (100%), as shown in Figure 2. For a given set of relative pump speed values, EPANET calculates flow and the corresponding specific energy demand used for pumping is then calculated for each pump within MS Excel using Equation 7, where w P,i is the specific energy demand needed for pumping and η i is the efficiency for a submersible well pump i.…”
Section: Hydraulic Modeling Of Groundwater Abstraction and Transportmentioning
confidence: 99%
“…The relations that govern pump operation at different rotational speeds are usually derived together with those that govern pump operation with different impeller diameters by the use of similitude theory, and are called affinity laws (Georgescu et al, 2014) as shown in Eqs 1 and 2:…”
Section: Pump Operation At Variable Speedsmentioning
confidence: 99%